Immunoprophylaxis of bovine respiratory syndrome - Rogan Dragan; Lazić Sava; Pavlović Radovan; Šamanc Horea (Veterinarski Glasnik, 2010)
Bovine Respiratory Syndrome (BRS) is a multifactorial disease caused by the interaction of infective agents, the environment and the individual immunological response of animals in the herd. Despite five decades of research on BRS, no clear understanding of how environmental factors influence pathogenic outcomes of the disease has been defined. As such, the development of immunoprophylaxis and vaccine programmes to prevent outbreaks of BRS in cattle has not been successful. The current paper discusses vaccination programmes for all categories of cattle and presents a review of existing vaccines being used for immunoprophylaxis of respiratory syndrome in cattle and discusses the advantages and disadvantages of the currently used vaccines and vaccination programmes. Lastly, a discussion detailing the design of future perfect vaccines is presented.